ANALISIS YURIDIS TERHADAP WAKAF TUNAI MENURUT UU NO. 41 TAHUN 2004 TENTANG WAKAF DALAM PERSFEKTIF FIKIH ISLAM (STUDI DI BAITUL MAL PIDIE JAYA) - BARON SIDIK S (PREMISE LAW JURNAL, 2016)
The word ‘Wakaf’ (Benefaction) literally means Habs (‘to endow’). It is like what was said by a Waqafa Yafiqu Waqafan, which means Habasa Yahbisu Habsan. Meanwhile, in Islamic view, a Wakaf means to endow one’s personal belongings or wealth and to grant its benefits in Allah’s (God’s) way. Cash wakaf is the wakaf made by an individual, a group of people, an institution or a legal entity in the form of cash. What is defined by ‘money’ includes securities such as shares, cheque, etc. The law of cash wakaf is still in debate by scholars; some scholars allow it while some others do not. The scholars who allow the cash wakaf are Imam al – Zuhri and Hanafi Sect. On the other hand; the scholars who do not allow cash wakaf are Ibn Abidin and Syafi’i Sect. Based on the research results, it can be seen: 1). Implementation of Cash Waqf in Islamic Fiqh Perspective is allowed origin of the money was invested in the effort for the results (mudaraba), then profits distributed in accordance with the purpose of waqf. Diwakafkan so that the money stays, while being delivered to mauquf 'alaih is the result of the development of the cash waqf. Meanwhile, according to Law No. 41 Year 2004 on Waqf that the management and development of properties, especially cash waqf endowments performed with Islamic principles. Among other things can be done through financing mudaraba, murabaha, musharakah, or Ijarah. 2). Empowerment cash waqf (money) for the welfare of the people there are four main benefits of cash waqf. Keywords: Cash Wakaf, Implementation of Cash Wakaf, Islamic principles.